Cholesteryl Ester Transfer Protein: The Key to Longevity? - Vijayakumaran, Vithooshan; Dattani, Neil D. (The Meducator, 2012)
The negative attributes of cholesterol receive much attention in the media and scientific literature, with good reason. However, there are aspects of cholesterol metabolism that actually reduce the risk of developing cardiovascular disease. Furthermore, variations in the gene for an important cholesterol transport protein may yield significant health benefits. This critical review outlines the basic physiology of cholesterol, discusses cholesteryl ester transfer protein and potential variations in its gene, and identifies the implications of current research in this field for the pharmaceutical industry.